PENGARUH AROMATERAPI KENANGA (CANANGA ODORATA) TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Silalahi, Kristina L.; Siregar, Patimah Sari; Ariga, Fajar (Jurnal Keperawatan Priority, 2020)
Hypertension is one of the biggest problems that cause death because many are undiagnosed and hypertensive sufferers often experience asymptomatic events causing difficulty to know the causes of hypertension. Treatment of hypertension can perform by pharmacology and non-pharmacology. Non-pharmacological treatment may be in the form of aromatherapy. This study aimed to determine the effect of aqueous aromatherapy on the decrease of blood pressure in hypertensive patients at Royal Prima Hospital Medan in 2017. The study design was quasi-experiment with one group pretest-postest design provided with aromatherapy for 10 minutes. The population consisted of 28 people. The 10 people as sampling were drawn by a purposive sampling technique. Data collection was performed by interview and observation. The bivariate analysis used was paired sample t-test with a significance level of 0.05 (5%). The results showed that the level of systolic and diastolic blood pressure before aromatherapy aqueous treatment was 156.60 mmHg and 92.40 mmHg. Systolic and diastolic blood pressure after aqueous aromatherapy administration was 142.60 mmHg and 81.80 mmHg. Based on the results of statistical tests it was found that there was a difference in blood pressure between before and after aromatherapy, {systolic, p-value = 0.000 (p <0.05) and diastolic, p-value = 0.000 (p <0.05)}. The results of this study concluded that there is an effect of giving aqueous aromatherapy (Kananga odorata) on the decrease of blood pressure in hypertension patients at Royal Prima Hospital Medan in 2017. It is suggested that aqueous aromatherapy can be applied as an alternative therapy to lower blood pressure.